Variability in fatty acids composition in eggs of an omnivorous waterbird, the black-headed gull Chroicocephalus ridibundus, foraging in different habitats - P. Indykiewicz; D. Jakubas; D. Kowalczyk-Pecka; I. Kitowski; M. Szady-Grad (The European Zoological Journal, 2023)
AbstractAnalysis of the qualitative signature of fatty acids in tissues of organisms is an increasingly utilized tool in studies of trophic ecology in aquatic and terrestrial ecosystems. Here, we studied a colonial waterbird, the black-headed gull Chroicocephalus ridibundus, nesting in three colonies. We aimed to investigate whether fatty acid composition of its eggs is affected by the location of the colony (reflecting the spatial variation in habitat composition and, in turn, female diet at the time of egg formation), and the egg laying sequence (reflecting the temporal variation in female diet). We found that the composition of fatty acids in eggs of black-headed gulls differed among colonies, but not among subsequent eggs within the clutch. We interpret these results in the context of spatial differences in the diet of females breeding in different colonies and a lack of temporal variation in the diet of individual females. The pattern of the ratio of omega-3 to omega-6 fatty acids reflected the contribution of aquatic/terrestrial prey to their diet, and was consistent with the area of water courses around the colonies. High levels of omega-6:omega-3 can promote inflammation and thus lead to increased susceptibility to antigens. Further studies with prey sampling are required to reconstruct the diet composition of females during egg formation in more detail.